Circularly‐polarised end‐fire antenna and arrays for 5G millimetre‐wave beam‐steering systems. Issue 9 (19th May 2020) - Al‐Amoodi, Khaled; Honari, Mohammad Mahdi; Mirzavand, Rashid; Melzer, Jordan; Elliott, Duncan G.; Mousavi, Pedram
Abstract : This study presents a circularly‐polarised substrate‐integrated waveguide end‐fire antenna and four‐antenna arrays for 5G beam‐steering mobile devices at 28 GHz. Polarisation is achieved through implementation of a substrate‐integrated waveguide notched‐septum polariser. It is then loaded with a dielectric lens to improve gain, axial ratio bandwidth, and circular polarisation (CP) purity. To suppress the mutual coupling between array elements, vias are extended on either side of the lens. It also improves the single‐element axial ratio and front‐to‐back ratio. The antenna's performance is found to be resilient to typical manufacturing tolerances for the lens and via extensions. The element and arrays are manufactured and measured. The prototypes demonstrated an impedance bandwidth of 11.4% with a maximum array gain of 10.5 dBi and a steering range of up to ± 35 ° (with reduced performance when steered to ± 45 ° ). Within this range, the antenna array demonstrates a gain variation of up to 3 dB and very good CP purity within the radiation half‐power beamwidths (HPBWs). A wide single‐element elevation HPBW of 95 ° is also demonstrated. Given its performance and ease of manufacture in a printed circuit board process, the proposed antenna could be a strong candidate for 5G millimetre‐wave beam‐steering systems.